Pollution affects Arabian and Saharan dust optical properties in the eastern Mediterranean - M. Teri; M. Teri; J. Gasteiger; J. Gasteiger; K. Heimerl; K. Heimerl; M. Dollner; M. Schöberl; M. Schöberl; P. Seibert; P. Seibert; A. Tipka; et al. (Atmospheric Chemistry and Physics, 2025)
Uncertainties in the direct radiative effect of mineral dust result from the variability in its optical properties but are also influenced by mixing with anthropogenic aerosols (“pollution”), e.g., black carbon or sulfates. This study investigates the effect of mixing pollution with mineral dust from different source regions on the intensive optical properties. The Ångström exponents of scattering and absorption, the single-scattering albedo, and the asymmetry parameter are determined from in situ measurements during the A-LIFE aircraft field experiment over the eastern Mediterranean, where Arabian and Saharan dust mixed with pollution. Our results show that all intensive dust optical properties change significantly with increasing pollution content, while differences between Arabian and Saharan dust are not statistically significant. We discuss the implications of these results for the identification of mineral dust events and for their direct radiative effects. The pollution masks the mineral dust signal, which calls for caution when using Ångström exponents to identify mineral dust events. Furthermore, the asymmetry parameter and single-scattering albedo change from pure to polluted mineral dust layers (e.g., at 525 nm, median values decrease from 0.67 to 0.56 and from 0.96 to 0.89, respectively). These changes have opposing effects on the shortwave direct radiative effect efficiency (i.e., the direct radiative effect per unit of aerosol optical depth), potentially canceling each other out. Still, the effect can be significant depending on surface albedo. In conclusion, quantifying pollution content in mineral dust layers is essential for accurately assessing their local direct radiative effect.